Linear relation between H i circular velocity and stellar velocity dispersion in early-type galaxies, and slope of the density profiles - Serra, P; Oosterloo, T; Cappellari, M; den Heijer, M; Józsa, G (Oxford University Press, 2016)
© 2016 The Authors Published by Oxford University Press on behalf of the Royal Astronomical Society. We report a tight linear relation between the H i circular velocity measured at 6 R e and the stellar velocity dispersion measured within 1 R e for a sample of 16 early-type galaxies with stellar mass between 1010 and 1011 M ⊙ . The key difference from previous studies is that we only use spatially resolved v circ (H i) measurements obtained at large radius for a sizeable sample of objects. We can therefore link a kinematical tracer of the gravitational potential in the dark-matter dominated outer regions of galaxies with one in the inner regions, where baryons control the distribution of mass. We find that v circ (H i)= 1.33 σ e with an observed scatter of just 12 per cent. This indicates a strong coupling between luminous and dark matter from the inner- to the outer regions of early-type galaxies, analogous to the situation in spirals and dwarf irregulars. The v circ (H i)-σ e relation is shallower than those based on v circ measurements obtained from stellar kinematics and modelling at smaller radius, implying that v circ declines with radius - as in bulge-dominated spirals. Indeed, the value of v circ (H i) is typically 25 per cent lower than the maximum v circ derived at ~0.2 R e from dynamical models. Under the assumption of power-law total density profiles ρ ∝ r -γ , our data imply an average logarithmic slope 〈γ〉 = 2.18 ± 0.03 across the sample, with a scatter of 0.11 around this value. The average slope and scatter agree with recent results obtained from stellar kinematics alone for a different sample of early-type galaxies.